ANALISIS PERUBAHAN LUASAN LAMUN DENGAN CITRA SATELIT SENTINEL-2A DI PESISIR KECAMATAN GUNUNG KIJANG, PULAU BINTAN - Wiweka Sabil Sianturi, Sena
Seagrass has many functions and benefits, especially for coastal areas, such as primary productivity, spawning grounds, breeding areas, food sources, and more. This makes seagrass management crucial. Seagrass management can be facilitated by the use of satellite imagery, which allows for monitoring seagrass over large areas in a short time. One of the satellite images that can be used is Sentinel-2A with a spatial resolution of 10 meters. This study will review the changes in seagrass coverage from 2020 to 2023, as well as seasonal changes during the western and eastern monsoons using data from 2019. Mapping seagrass with satellite imagery can be made easier using the Depth Invariant Index method, which is a method for reducing the effects of the water column, allowing objects to be accurately identified even beneath the water surface. According to the study, seagrass coverage along the Gunung Kijang coast tends to fluctuate with a decreasing trend, indicating that seagrass coverage is likely to continue to decline in the coming years. The seagrass area along the Gunung Kijang coast experienced a degradation of 262.26 hectares from 2020 to 2023, with an annual degradation rate of 87.42 hectares per year, representing a 13.02% decline. The decline in seagrass coverage along the Gunung Kijang coast is primarily due to a decrease in the oceanographic parameter of salinity, causing salinity levels to fall outside the optimal range for seagrass. There were also changes in coverage during the western and eastern monsoons, where seagrass coverage was smaller during the western monsoon due to seagrass being covered by sand, as indicated by the higher current speeds during the western monsoon. Additionally, the changes in coverage may also be attributed to certain human activities in the area.